2022
DOI: 10.1111/1346-8138.16398
|View full text |Cite
|
Sign up to set email alerts
|

Severe cutaneous adverse reactions associated with systemic ivermectin: A pharmacovigilance analysis

Abstract: Despite poor evidence, the antiparasitic ivermectin has been advocated as a potential COVID‐19 therapy. This has led to a rise in calls to poison‐control centers by people self‐medicating with ivermectin, which is sold over the counter for veterinary uses. We aimed to investigate the association between severe cutaneous adverse reactions (SCARs) and ivermectin. Postmarketing data from the FDA Adverse Event Reporting System (FAERS), gathered between 2014 and 2021, was employed to detect disproportional signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For the aforementioned reason, in this study, we introduced the pharmacovigilance method as a more uniform metric for risk assessments to evaluate the ADR signals of each drug at the SMQ and PT levels. Although there have been studies using signal mining methods to assess the risk of drugs causing SCARs, the scope of the research is limited to specific drug classes or SCAR subclasses (Xu et al, 2021;Zhu et al, 2021;Bomze et al, 2022), so that the risk comparison between drugs can only be achieved within a limited range. In this study, we extended this scope to all reported culprit-drugs to date, allowing for cross-drug class, cross-PT risk Frontiers in Pharmacology frontiersin.org assessment (Supplementary Table S1), which is more applicable to rapidly assess the risk of drugs causing SCARs in clinical practice.…”
Section: Adverse Reaction Signal Detection Resultsmentioning
confidence: 99%
“…For the aforementioned reason, in this study, we introduced the pharmacovigilance method as a more uniform metric for risk assessments to evaluate the ADR signals of each drug at the SMQ and PT levels. Although there have been studies using signal mining methods to assess the risk of drugs causing SCARs, the scope of the research is limited to specific drug classes or SCAR subclasses (Xu et al, 2021;Zhu et al, 2021;Bomze et al, 2022), so that the risk comparison between drugs can only be achieved within a limited range. In this study, we extended this scope to all reported culprit-drugs to date, allowing for cross-drug class, cross-PT risk Frontiers in Pharmacology frontiersin.org assessment (Supplementary Table S1), which is more applicable to rapidly assess the risk of drugs causing SCARs in clinical practice.…”
Section: Adverse Reaction Signal Detection Resultsmentioning
confidence: 99%
“…A drug eruption to ivermectin cannot be excluded; however, cutaneous adverse reactions associated with systemic ivermectin are rare. 6 , 7 , 8 , 9 A drug eruption would not be limited to both hands and feet but would involve the whole body. Id reaction was suspected because hands and feet skin manifestations were associated with the plantar inflammatory CLM after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Prior case-control studies in Europe (EuroSCAR) and smaller studies exploring the association of individual medications have been performed to establish the classically implicated medications in SCARs. [8][9][10][11][12][13][14][15][16][17] However, a comprehensive analysis of medications with association with SJS, TEN, DRESS, and AGEP using data from The United States Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) has not been completed. The goal of this study is to examine all 4 categories of SCARs using FAERS and provide an updated and stratified list of medications with significant reporting odds ratios (RORs).…”
Section: Introductionmentioning
confidence: 99%